1986
DOI: 10.1016/s0735-1097(86)80116-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of warfarin and adjusted subcutaneous heparin during pregnancy in patients with an artificial heart valve

Abstract: Adjusted subcutaneous heparin was used for thromboembolism prophylaxis during 18 pregnancies in 16 women with an artificial heart valve. Oral warfarin was replaced by subcutaneous heparin as soon as pregnancy was confirmed. The dosage of heparin was adjusted to maintain a partial thromboplastin time at 1.5 times the control value and treatment was administered during the first trimester and the last 3 weeks of gestation. Warfarin was used between the 13th and 37th week. There were no maternal thromboembolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 14 publications
0
9
0
5
Order By: Relevance
“…Twenty studies ‡ reported switching to hep-*References 7 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][33][34][35]37,38,40,41. †References 9,22,24,28,30,32,[34][35][36]38,39,42. ‡References 8,9,[19][20][21][22]24,[26][27][28][29][30][31][33][34][35]37,38,40,41.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies ‡ reported switching to hep-*References 7 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][33][34][35]37,38,40,41. †References 9,22,24,28,30,32,[34][35][36]38,39,42. ‡References 8,9,[19][20][21][22]24,[26][27][28][29][30][31][33][34][35]37,38,40,41.…”
Section: Resultsmentioning
confidence: 99%
“…Dans la littérature, le pourcentage de thrombose prothétique varie entre 0 et 9,2 % [13, [16][17][18][19]. Nos résul-tats, comme ceux de Sareli et al [18], s'expliqueraient par l'utilisation de prothèses mécaniques récentes, type Saint-Jude, réputées peu thrombogènes, dont 62,5 % de nos patientes étaient porteuses.…”
Section: Discussionunclassified
“…Le risque thromboembo- Iturbe-Alessio et al [12] avaient trouvé un taux de 13,2 % d'hémorragie sous héparine. Lee et al [17] rapportaient deux cas d'hémorragie de la délivrance massive sous anticoagulants. Ce type d'accident était évalué à un taux d'environ 8 % dans le péripartum pour l'héparine et les AVK.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Antiplatelet agents have also been evaluated as substitutes for warfarin during gestation and were found to be associated with a high risk (20%) of cerebral embolism [32]. Conflicting results have been reported in evaluating the use of adjusted dose heparin to maintain an aPTT level of 1.5 to 2.5 times normal during the 6th to 12th weeks of gestation with respect to the risk of thrombotic and thromboembolic complications [33][34][35]. These studies are limited due to use of older-generation valve prosthesis as well as use of low doses of heparin [2••].…”
Section: Special Considerationsmentioning
confidence: 99%